Stone sky Gold Mountain - Riwoe, Mirandi (University of Queensland Press, 2020)
Set during the gold-rush era in Australia, this beautifully written historical novel about Chinese diggers in North Queensland is full of unforgettable characters, and explores timeless questions of exile, belonging and identity. Tragic family circumstances force siblings Ying and Lai Yue to flee their home in China to seek their fortunes in North Queensland. Life on the gold fields is hard, and they soon abandon the diggings and head to nearby Maytown. Once there, Lai Yue finds a job as a carrier on expeditions, taking him far away from his sister. Ying remains in the township, where she works in a local store and strikes up an unlikely friendship with Meriem, a young white woman with a troubled past. Maytown is a place where violence frequently erupts and, when a serious crime is committed, suspicion falls on all those who are considered outsiders. Evoking the rich, unfolding tapestry of Australian life in the late nineteenth century, Stone Sky Gold Mountain is a heartbreaking and timeless story about those exiled from family and place who encounter discrimination yet yearn for acceptance.